Organology of Traditional Music Instrument of Pelle’ (Universitas Negeri Semarang, 2022)
The background of this paper is the production process to describe Pelle's traditional musical instrument structurally and functionally. In conducting this organological study, theories on ethnomusicology were used, which discussed the relationship between music and culture by conducting field research. Researchers used qualitative research methods with an ethnomusicology discipline approach, with laboratory work and field studies with observation, interviews, and documentation techniques. From the research results, the Pelle' musical instrument has a size of 3-4 cm and is made from Dalame Pare rice stalks. Then at the end of the Pelle', 10-12 palm leaves are wrapped around, which are made to resemble a trumpet. The Pelle' musical instrument is often played during the harvest season. As the development of the Pelle' musical instrument is currently used at the Rambu Tuka’ ceremony, which is related to a special thanksgiving event at the Mangrara Banua Tongkonan event. Structurally and functionally, the Pelle' musical instrument has uses and functions in society both as entertainment and as part of the Rambu Tuka' custom.